2021
DOI: 10.3390/infrastructures6020023
|View full text |Cite
|
Sign up to set email alerts
|

GNSS (GPS) Monitoring of Dynamic Deflections of Bridges: Structural Constraints and Metrological Limitations

Abstract: The advent of modern geodetic satellite techniques (GNSS, including GPS) permitted to observe dynamic deflections of bridges, initially of long flexible ones, and more recently of short, essentially stiff bridges with modal frequencies > 1 Hz, and with small SNR (signal-to-noise ratio), even SNR < 1. This was an enormous progress, but not without problems. Apart from monitoring results consistent with structural models, experimental data and serviceability criteria, there exist some apparently unexplaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(64 reference statements)
0
9
0
1
Order By: Relevance
“…Liên quan tới lĩnh vực quan trắc, nghiên cứu [1,8] đã thống kê hàng loạt các công trình lớn được quan trắc bằng công nghệ GNSS bao gồm nhà cao tầng [9,10], ống khói [11,12], đập, các tòa tháp [13,14] hay các cây cầu có quy mô lớn [15,16] với các kỹ thuật đo động thời gian thực GNSS-RTK trạm đơn, đo động xử lý sau (PPK), đo động thời gian thực với hệ thống trạm tham chiếu hoạt động liên tục (Net-RTK) và phương pháp PPP [1]. Trong các hệ thống quan trắc sức khỏe kết cấu đã được triển khai, hệ thống GNSS đóng vai trò then chốt để đánh giá tình trạng an toàn của kết cấu [17][18][19] và quá trình vận hành, bảo trì sẽ bị ảnh hưởng nếu kết quả có chứa sai số lớn.…”
Section: Giới Thiệuunclassified
“…Liên quan tới lĩnh vực quan trắc, nghiên cứu [1,8] đã thống kê hàng loạt các công trình lớn được quan trắc bằng công nghệ GNSS bao gồm nhà cao tầng [9,10], ống khói [11,12], đập, các tòa tháp [13,14] hay các cây cầu có quy mô lớn [15,16] với các kỹ thuật đo động thời gian thực GNSS-RTK trạm đơn, đo động xử lý sau (PPK), đo động thời gian thực với hệ thống trạm tham chiếu hoạt động liên tục (Net-RTK) và phương pháp PPP [1]. Trong các hệ thống quan trắc sức khỏe kết cấu đã được triển khai, hệ thống GNSS đóng vai trò then chốt để đánh giá tình trạng an toàn của kết cấu [17][18][19] và quá trình vận hành, bảo trì sẽ bị ảnh hưởng nếu kết quả có chứa sai số lớn.…”
Section: Giới Thiệuunclassified
“…As shown in [12], a small amount of outliers frequently occurs in measured signals during field tests, and the corresponding data set was referred to as "bad data." The WAM had the advantage of minimizing the effect of outliers on DLA.…”
Section: Ability To Resist Outliersmentioning
confidence: 99%
“…Therefore, we have proposed the weighted average method (WAM) to address the above issues [11]. In addition, unrealistic responses of the bridge have been monitored recently, as shown in [12]. Deflections were contaminated by two high-frequency peaks, which are important for calculating DLA.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et all [12] indicated that GNSS can be used to determine the dynamic character in the oscillation of the bridge and decisions of the maintenance procedure are supported by GNSS monitoring results. However, although GNSS had much progress in long-time monitoring, the sampling rate of the GNSS devices cannot meet the requirement, consist of a variety of noises [12], and can lead to some differences in the monitoring results [13]. Thus, a combination of GNSS and sensors is needed to interpret the bridge displacement better [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a combination of GNSS and sensors is needed to interpret the bridge displacement better [14,15]. Some limitations of the GNSS were also mentioned in the studies [9,13] such as low sampling rate, and influences of the weather conditions, and both gave a conclusion that it is necessary to have a suitable solution to identify dynamic characteristics. Yu et all [16] used a multimode adaptive filter algorithm to identify the dynamic displacement and modal frequencies with data from GNSS and accelerometer.…”
Section: Introductionmentioning
confidence: 99%